Penerapan Kegiatan Bermain Peran untuk Meningkatkan Kemampuan Berbicara Anak di TK GMIM Musafir Kleak Manado - Eduard Jeconya Lengkong (Peneliti.net, 2022)
Seeing how useful role playing activities are in improving children's speaking skills, the author wants to conduct a study with the title of implementing role playing activities to improve children's speaking skills in Musafir Kleak Kindergarten. The purpose of this study was to find out how the implementation of role playing activities in improving children's speaking skills in Musafir Kleak Kindergarten. This research uses Classroom Action Research (CAR). The research method is classroom action research which refers to the research model of Kemmis and Mc. Taggart, 1988 (Trianto, 2001:17) with the following stages of research: action planning, action implementation, observation, and reflection. The subjects in this study were students in GMIM Musafir Kleak Manado Kindergarten with a total of 20 students. Sources of data are students and teachers at GMIM Musafir Kleak Manado Kindergarten, while the data collection technique is through field notes. The data in this study were collected in several ways, namely observation and document analysis. The time of the research is carried out for 4 (four) months. The place of research was carried out at GMIM Musafir Kleak Kindergarten, Manado. The success rate of the implementation of cycle 1 is 68% of children actively participating in learning, while in cycle 2, children are successful 85%. If the two cycles were compared, cycle 2 was more successful than cycle 1. Looking at the results of this classroom action research, it can be said that this role playing method is good to be applied in learning, especially in developing speaking and language skills. However, it must be considered in the provision of role-playing tools that can attract children's interest, even though the tool or media is in the simplest form. Based on the results of these studies, it can be concluded that learning by using the role playing method that is done well can improve speaking skills in group B children of GMIM Musafir Kleak Kindergarten